Methylation alterations at imprinted genes detected among long‐term shiftworkers. (28th November 2012) - Jacobs, Daniel I.; Hansen, Johnni; Fu, Alan; Stevens, Richard G.; Tjonneland, Anne; Vogel, Ulla B.; Zheng, Tongzhang; Zhu, Yong
Abstract Exposure to light at night through shiftwork has been linked to alterations in DNA methylation and increased risk of cancer development. Using an Illumina Infinium Methylation Assay, we analyzed methylation levels of 397 CpG sites in the promoter regions of 56 normally imprinted genes to investigate whether shiftwork is associated with alteration of methylation patterns. Methylation was significantly higher at 20 CpG sites and significantly lower at 30 CpG sites (P < 0.05) in 10 female long‐term shiftworkers as compared to 10 female age‐ and folate intake‐matched day workers. The strongest evidence for altered methylation patterns in shiftworkers was observed for DLX5, IGF2AS, and TP73 based on the magnitude of methylation change and consistency in the direction of change across multiple CpG sites, and consistent results were observed using quantitative DNA methylation analysis. We conclude that long‐term shiftwork may alter methylation patterns at imprinted genes, which may be an important mechanism by which shiftwork has carcinogenic potential and warrants further investigation. Environ. Mol. Mutagen., 2013. © 2012 Wiley Periodicals, Inc.